Penilain Aplikasi Veryeasy Accounting Solution Pada Apotik Sari Murah Dengan Metode UAT - Sandri Sagitarius Sarumaha; Ahmad Taufik (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the development of an information system in a pharmacy that still uses Very Easy Accounting Solution 1.0. This system is an accounting software designed to help users manage business accounting finances in a simple way and the system is still the first version of an accounting solution with basic features usually found in accounting systems such as creating financial reports, recording transactions, managing inventory, payroll and bill payments. This research will make improvements to the recording system using a computer-based system, both in terms of inventory data collection, transaction data recording, and other processes related to activities at the pharmacy in question. This research also discusses system analysis, namely activities to look at systems that are already running, see what is good and what is not good, and then document the needs that will be met in the new system. Apart from that, this research also discusses UAT (User Acceptance Testing) which is used as the final step in application development to meet user needs, aspirations and input which can become material for future application development and improvement..